Pengembangan Media Pembelajaran Flash Card Menggunakan Aplikasi Canva pada Tema 8 Kelas IV SDN 010100 Bangun Sari T.A 2022/2023 - Nopita Sari Sinaga; Eva Betty Simanjuntak (Journal on Education, 2023)
This study aims to determine: the validity, practicality, and effectiveness of flash card learning media in learning on theme 8 sub-theme 1 learning 3 in class IV SD Negeri 010100 Bangun Sari T.A 2022/2023. This type of research is research and development (R&D) using a 4-D model which consists of four stages, namely the defining, designing, developing, and disseminating stages. The subjects in this study were 12 class IV students at SD Negeri 010100 Bangun Sari. Data collection techniques in this study used interviews, questionnaires, and pretest and posttest question sheets. The results of this study were (1) the flash card media validity test obtained a value of 87% with very valid criteria, and the material validity test obtained a value of 85% with very valid criteria, (2) the flash card practicality test obtained a value of 88% with the criteria very practical, (3) the effectiveness test of flash cards showed that there was an increase in learning outcomes before and after using the media in learning, and by calculating the effectiveness of the product, it obtained 83% with very effective criteria. From the results of this study it can be concluded that the development of flash card learning media using the Canva application on theme 8 sub-theme 1 learning 3 meets the criteria of very valid, very practical, and very effective.